Resistin-Induced Endoplasmic Reticulum Stress Contributes to the Impairment of Insulin Signaling in Endothelium - Luo, Jun; Huang, Lei; Wang, Aimei; Liu, Yueyang; Cai, Ruiping; Li, Weihong; Zhou, Ming-Sheng (Frontiers in Pharmacology, 2018)
Background: Endoplasmic reticulum (ER) stress plays an important role in the pathogenesis of obesity, insulin resistance and cardiovascular diseases (CVDs). Impairment of insulin vascular action may represent a mechanism linking insulin resistance and CVDs. The present study tested the hypothesis that adipocyte-derived resistin inhibits insulin-stimulated endothelial NO production through the induction of ER stress. Methods and Results: Human umbilical vein endothelial cells were incubated with tunicamycin (an inducer of ER stress, 1-20 g/mL) or resistin (10-100 ng/mL) for 1 hour. Either tunicamycin or resistin increased GRP78 (an ER stress marker) expression associated with the impairment of insulin-stimulated Akt/eNOS phosphorylation, which were prevented by TUDCA (an ER stress suppressor). Resistin increased reactive oxygen species (ROS) production, antioxidant treatment inhibited resistin-induced GRP78 expression and impairment of insulin Akt/eNOS signaling, suggesting that ROS may involve resistin-induced ER stress. Resistin also increased JNK phosphorylation, which was prevented by TUDCA. JNK inhibitor SP600125 relieved the resistin inhibitory effects on endothelial insulin Akt/eNOS signaling. In ex vivo experiments, the incubation of aortic rings with resistin impaired insulin- but not acetylcholine-induced vasodilation, which was restored by TUDCA. LNAME (a NOS inhibitor) abolished insulin-induced vasorelaxation in the control or the resistin-treated aortic rings. In addition, resistin increased the mRNA expressions of proinflammatory cytokines tumor nuclear factor (TNF) and interleukin (IL)-1, which were also prevented by TUDCA. Conclusion: Our results support the ideal that ER stress may play an important role for resistin impairment of vascular insulin signaling and insulin action. The mitigation of ER stress may represent a new strategy for prevention and treatment of CVDs in obesity and insulin resistant-related diseases.